Time stamped list mode data from gamma-ray spectroscopic measurements on 47 nuclear fuel assemblies performed at Clab, Sweden, September 2016 through March 2019 - Jansson, Peter; Bengtsson, Martin; Bäckström, Ulrika; Grape, Sophie; Branger, Erik; Sjöland, Anders (Uppsala University, 2020)
Data were collected by saving list-mode detector data during acquisitions. Two types of measurements were performed; Measurements with nuclear fuel assemblies present and background measurements without the fuel assemblies. Background measurements were performed in sequences of about 10 min acquisitions. The fuel assemblies were positioned in the water pool and axially moved during acquisition in front of a collimator built into the pool wall, rotated so that one of its four corners points towards the detector. The 137Cs calibration source was positioned along the centre line of the collimator slit both during background and fuel measurements. The detector and associated electronics were located in a room adjacent to the pool.

Measurement data is saved in a text format. The text format is structured as a measurement header, followed by a sequence of one or more meta-batches. Each meta-batch is structured as a sequence of one or more event data batches. Each event data batch is structured as an event batch header, followed by one or more event data lines and an event batch footer.

The dataset was originally published in DiVA and moved to SND in 2024.

Data were collected by saving list-mode detector data during acquisitions. Two types of measurements were performed; Measurements with nuclear fuel assemblies present and background measurements without the fuel assemblies. Background measurements were performed in sequences of about 10 min acquisitions. The fuel assemblies were positioned in the water pool and axially moved during acquisition in front of a collimator built into the pool wall, rotated so that one of its four corners points towards the detector. The 137Cs calibration source was positioned along the centre line of the collimator slit both during background and fuel measurements. The detector and associated electronics were located in a room adjacent to the pool.

Measurement data is saved in a text format. The text format is structured as a measurement header, followed by a sequence of one or more meta-batches. Each meta-batch is structured as a sequence of one or more event data batches. Each event data batch is structured as an event batch header, followed by one or more event data lines and an event batch footer.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Time stamped list mode data from gamma-ray spectroscopic measurements on 47 nuclear fuel assemblies performed at Clab, Sweden, September 2016 through March 2019
Keywords: radiation; radiation; spectroscopy; spectroscopy; HPGe; HPGe; Physics with specialization in Applied Nuclear Physics; Physics with specialization in Applied Nuclear Physics; spent nuclear fuel; spent nuclear fuel; axial scanning; axial scanning; list mode; list mode; gamma; gamma; Cs-137; Cs-137; Subatomic Physics; Subatomär fysik